The Influence of Principal Behavioral Decision Making Style on Teacher Work Behavior - Tika Widiyan; Zurohma Hasna Rohiilah; Safiyah Riyantini; Imam Cahyono; Salfen Hasri; Sohiron Sohiron (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study was to examine the effect of the principal's behavioral decision-making style on the work behavior of teachers. This type of research is quantitative with a population of 17 people, 1 principal and 16 teachers. The sampling technique used is the saturated sample technique. Data collection techniques used instruments in the form of questionnaires and data analysis techniques to test hypotheses using Product Moment correlation analysis and simple regression testing with the help of SPSS 21 of Windows. The results of this study indicate that the rxy value of 0.697 is greater than the rtable value both at a significance level of 5% (0.497) and a significance level of 1% (0.623), namely 0.497 <0.697> 0.623. Then Ha is accepted and H0 is rejected, meaning that there is a significant influence between the principal's behavioral taking style and the teacher's work behavior. In a simple regression test, the equation Y = 11,161 + 1.117X, if the behavioral decision-making style increases by 1 point, then the value of work behavior increases by 1.117 at the constant 11,161, and becomes 55,841 when the behavioral decision-making style is optimized. The value of R Square is 0.462, which means that the influence of behavioral decision-making style on teacher work behavior is 46.2%, and the remaining 53.8% is caused by other variables that are not the focus of discussion in this study.